Interacting with information and robotics systems - Pentiuc, S.G.; Vatavu, R.D.; Ungurean, O.C.; Laurent, G.; Christophe, C.; De Backer, L.; De Strycker, L.; Hamburg, Il. (Оптико-електронні інформаційно-енергетичні технології, 2008)
The aim of this paper is to present the results obtained during the project 131-CEEX/2006, INTEROB: Interacting by Gestures with Information and Robotics Systems for the time frame 2006-2008. The project focused on natural interaction using gesture recognition technology applied in various applications such as: virtual environments, augmented reality, collaborative working and interaction with robotics systems.